Teori Perkembangan Kognitif Jean Piaget dan Implementasinya Dalam Pembelajaran di SD/MI - Mifroh, Nazilatul (JPT : Jurnal Pendidikan Tematik, 2020)
Every human being will always feel the development, including the basic age children aged between 7 and 12 years. In its development there are several aspects that are urgent, including cognitive development or the development of knowledge of the mind. Cognitive development is something that is always increasing or developing which is related to thoughts such as reasoning, ideas, imagination and creative memories. In elementary age children who sit in elementary school experience 2 stages of cognitive development, namely the concrete operational stage and formal operational stage. Although there are at the same stage, cognitive development in primary age children at each age level has a different cognitive development. This needs to be understood in the educational environment with the need for teaching and learning activities in the classroom. Understanding the importance of the ability of cognition in children is nothing but for the needs in the selection of materials, strategies, models and methods that are appropriate. In this study using a qualitative approach and data analysis using descriptive methods. The aim of this research is to create an effective teaching and learning activity in the classroom and students understand easily the material presented by the teacher optimally based on the cognitive stage they experience.